2021
DOI: 10.1080/21655979.2021.2002498
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223-3p is involved in fracture healing by regulating fibroblast growth factor receptor 2

Abstract: MicroRNAs (miRNAs) are powerful modulators of fracture healing. The research explored the level of serum miR-223-3p in fracture patients and its potential mechanism in fracture healing. In the study, miR-223-3p levels in 42 patients with intra-articular fracture and 40 patients with hand fracture were detected by real-time fluorescence quantitative PCR reaction (qRT-PCR). Subsequently, osteoblasts MC3T3-E1 was transfected with miR-223-3p mimic or inhibitor, and cell function was detected by Cell counting kit (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The FGFR2 gene encodes a protein that is a member of the fibroblast growth factor receptor (FGFR) family [ 27 ]. FGFR2 was shown to be involved in biological processes such as cell proliferation, migration, tube formation and anti-inflammation in previous studies [ 28 , 29 ]. Our data revealed that overexpression of FGFR2 restored hRMECs function under HG and miR-524-5p overexpression conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The FGFR2 gene encodes a protein that is a member of the fibroblast growth factor receptor (FGFR) family [ 27 ]. FGFR2 was shown to be involved in biological processes such as cell proliferation, migration, tube formation and anti-inflammation in previous studies [ 28 , 29 ]. Our data revealed that overexpression of FGFR2 restored hRMECs function under HG and miR-524-5p overexpression conditions.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-223 was first identified in haematopoietic cells [ 19 ]. Its abnormal expression in many disorders has been widely studied in recent years [ 20 ]. Previously, miR-223 was reported to be involved in the regulation of infections, immune response and several inflammatory disorders [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-223 has been proven to be a powerful regulatory RNA in the field of bone biology [ 20 ]. Numerous studies documented the potential function of miR-223 in controlling osteoblast differentiation and stimulating differentiation of osteoclasts [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of osteoblasts is to synthesize bone matrix, which is differentiated from ABMSCs [ 25 , 26 ]. The process of fracture healing requires the production of a large number of new osteoblasts, which accelerates bone synthesis and calcification, and increases bone volume and density [ 27 ]. As the body ages, the number of ABMSCs functional cells decreases, and their potential to differentiate into osteoblasts in the bone marrow is down-regulated [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%